2010
DOI: 10.1021/nl102684x
|View full text |Cite
|
Sign up to set email alerts
|

Highly Strained Compliant Optical Metamaterials with Large Frequency Tunability

Abstract: *These authors contributed equally to this work. SUPPORTING INFORMATION:Coupled systems composed of asymmetric resonator elements have symmetric and antisymmetric resonances. In the manuscript, only the antisymmetric resonances are reported for the SRR-bar and ACSRR cases, as the amount of tuning is larger and more strongly dependent on the coupling distance than for the symmetric resonance. In Figure S1, the wavelength range is extended in order to show how both the symmetric and the antisymmetric mode are af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
386
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 389 publications
(399 citation statements)
references
References 36 publications
5
386
0
2
Order By: Relevance
“…21 Incorporating resonant elements on stretchable substrates enables mechanical tuning of the optical responses of metasurfaces. [22][23][24] Additionally, in many metasurface designs, nonlinear materials have been introduced into resonant electromagnetic fields to enhance tunable higher-order harmonic generation. 25,26 Apart from the tunability, efficiency is another factor to consider for metasurface in real-world applications.…”
Section: Abstract: Nanophotonics · Stretchable Electronics · Subwavelmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Incorporating resonant elements on stretchable substrates enables mechanical tuning of the optical responses of metasurfaces. [22][23][24] Additionally, in many metasurface designs, nonlinear materials have been introduced into resonant electromagnetic fields to enhance tunable higher-order harmonic generation. 25,26 Apart from the tunability, efficiency is another factor to consider for metasurface in real-world applications.…”
Section: Abstract: Nanophotonics · Stretchable Electronics · Subwavelmentioning
confidence: 99%
“…The elastomeric matrix, namely polydimethylsiloxane (PDMS), is commonly used in stretchable technologies 22,37 as a flexible substrate due to its remarkable elasticity and low optical losses.…”
Section: Abstract: Nanophotonics · Stretchable Electronics · Subwavelmentioning
confidence: 99%
“…Alternative methods for high-resolution patterning of soft polymers have found some success, and include nano-imprint lithography or stamping 23,24 , and self-assembly 1,25 ; these methods allow for highly parallelized fabrication of submicron structures on polymer substrates. All such approaches pose problems for fabrication of implantable microdevices, including difficulties aligning multi-layer patterns, restrictions on material choice, and for nano-imprint lithography, use of high temperatures and pressures, which can deform polymer substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Fano resonances in plasmonic structures are of great recent interest 7,[32][33][34][35][36][37][38][39][40] . It is suggested that their sharp characteristic spectral features and sensitivity to the sample parameters may turn them into efficient sensors.…”
mentioning
confidence: 99%